Strategic Thinking and Reasoning in Integer Knowledge Enhancement (Strike): Manipulative Tool in Enhancing Integer Operations - Ryan L Dumaguin; Rocel A. Turco; Richel B. Rabas; Ramir G. Pacheco; Emma O. Cajurao; Rio A. Villarias (Future Science / FSH-PH Publications, 2026)
This study evaluated the effectiveness of the Strategic Thinking and Reasoning in Integer Knowledge Enhancement (STRIKE) manipulative tool in improving the integer operation skills of Grade 9 learners at Lantangan National High School. A quantitative pre-experimental one-group pretest–posttest design was employed involving 30 purposively selected Grade 9 learners who obtained the lowest scores in the Integer Test of Primary Operations (ITPO). Participants received a two-week intervention using the STRIKE manipulative tool before completing the posttest. Descriptive statistics were used to summarize learners' performance, while paired-samples and independent-samples t-tests determined significant differences in achievement. Results revealed significant improvements in both male learners (t = −6.9099, p < .05) and female learners (t = −12.435, p < .05) following the intervention. Although female learners obtained a slightly higher mean posttest score than male learners, no statistically significant difference was found between the two groups (t = 1.9999, p = .0553). The findings suggest that the STRIKE manipulative tool is an effective instructional intervention for improving Grade 9 learners' performance in integer operations by enhancing their conceptual understanding and computational proficiency while providing equitable learning opportunities regardless of sex. Future studies are recommended to employ larger samples and experimental or quasi-experimental designs with comparison groups to further validate its effectiveness.